Intercultural Awareness in English Education: Bridging Cultures for Effective Teaching and Learning in Ghana - Agbevivi, Shine Lillian Gifty; Bukari, Francis; Klu, Ernest Kwesi (Universitas Lancang Kuning, 2025)
Teachers understanding of culture diversity in the classroom is key to promoting learning. Therefore, there is the need for teachers to develop and implement effective pedagogical practices that foster intercultural competence in the Classroom. However, available literature suggests that while abundant anecdotal and perceptual evidence exists about the importance of understanding diversity in English as a second language classroom, information on teachers’ intercultural competence and prevalence of culturally responsive teaching practices among English language teachers is inadequate. This study therefore examined the intercultural competence teaching practices in English language classrooms in Ghanaian classrooms. Adopting the Socio-cultural Theory within a quantitative approach with a descriptive survey design, a sample of 154 English language teachers were randomly sampled from basic schools in Awutu-Senya-East municipality of Ghana. The results reveal that English language teachers in the municipality recognize the significance of intercultural competence and demonstrate capabilities to integrate culturally responsive teaching strategies within their classrooms. Furthermore, the findings indicate variations in confidence levels and practical implementation, particularly in adapting teaching methods to diverse cultural learning styles and accessing support and resources necessary for these adaptations. The findings imply that occasional but frequent professional development seminars and training sessions centred on intercultural competency teaching methods for English language teachers be carried out. Additionally, School Improvement and Support Officers (SISOs) should be trained to equip them with the knowledge to ensure constant prompting of teachers.